2020
DOI: 10.3164/jcbn.19-121
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin induced NUPR1-dependent autophagic cell death by disturbing reactive oxygen species homeostasis in osteosarcoma cells

Abstract: Osteosarcoma is a primary bone aggressive cancer, affecting adolescents worldwide. Quercetin (a natural polyphenolic com pound) is a polyphenolic flavonoid compound found in a variety of plants. It has been demonstrated to exert cytostatic activity against a variety of human cancer, including the human osteo sarcoma. However, its efficacy in the treatment of osteosarcoma and the underlying antitumor mechanism has not been fully elucidated yet. In this study, we exposed MG 63 cells to different concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…These data suggest that HERV-K env KO and down-regulation of NUPR1 may regulate the protein stability of RB protein. The functions of NUPR1 have been reported to be highly related to ROS generation, apoptosis induced by autophagy, and ER stress [26,27]. Therefore, the ROS-NUPR1 pathway was analyzed via ROS levels and related protein levels in HERV-K env KO cells.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that HERV-K env KO and down-regulation of NUPR1 may regulate the protein stability of RB protein. The functions of NUPR1 have been reported to be highly related to ROS generation, apoptosis induced by autophagy, and ER stress [26,27]. Therefore, the ROS-NUPR1 pathway was analyzed via ROS levels and related protein levels in HERV-K env KO cells.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that quercetin-induced overproduction of ROS led to increased expression and activation of NUPR1. Although a majority of the studies show an inverse relation between NUPR1 and ROS, a direct relation is hypothesized [ 115 , 116 ].…”
Section: Phytochemicals: a Promising Role In Ros Mediated Cancer Cmentioning
confidence: 99%
“…In addition, the co-treatment further enhanced quercetin-mediated LC3B expression along with an increase in p62, indicating that lysosomal inhibition plays a significant role in the death of glioma cells [ 164 ]. In osteosarcoma cells, quercetin treatment augmented NUPR-1-mediated autophagic cell death accompanied by the increase in ROS level [ 165 ]. Evidence indicates that NUPR-1 helps in the transcriptional activation of genes involved in autophagosome formation and is also involved in cell cycle regulation, DNA repair and apoptosis [ 166 , 167 ].…”
Section: Roles Of Polyphenols In Autophagic Adaptation For Healthy Agingmentioning
confidence: 99%